A high-throughput approach to evaluating NCp7 RNA binding activity for HIV-1 drug discovery - Joanna K. Winstone; Rikki Uhrich; Thibault Alle; Brian C. Kraemer (SLAS Discovery)
The HIV-1 epidemic broadly impacts healthcare. There remains a continued need for improved anti-viral therapies resilient to the development of drug resistance. HIV-1 nucleocapsid protein 7 (NCp7) seems a prime drug target due to its unique nucleic acid chaperone activity required for multiple viral processes. NCp7 RNA binding activity has been shown to increase viral production and infectivity within the host. Here we introduce a high-throughput AlphaScreen assay to evaluate NCp7 RNA binding activity and validate its specificity and sensitivity using a known inhibitor. We also demonstrate the utility of this assay by performing a drug-repurposing screen, which identified seven confirmed inhibitors of NCp7 RNA binding and two confirmed enhancers of NCp7 RNA binding. This tool will aid in future NCp7-targeted drug discovery initiatives for the treatment of HIV-1 infection.